Theory and Practice of Model Transformations 6th International Conference, ICMT 2013, Budapest, Hungary, June 18-19, 2013. Proceedings - Duddy, Keith; Kappel, Gerti; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 6th International Conference on Theory and Practice of Model Transformations, ICMT 2013, held in Budapest, Hungary, in June 2013. The 13 full papers and 5 tool and application demonstrations were carefully selected from 58 submissions. The papers are grouped in topical sections which focus on new programming models, tools and applications, evolution and synchronization, transformation engineering, and testing.
Mining Models from Generated System Tests -- Streaming model transformations: scenarios, challenges and initial solutions -- Genetic-Programming Approach to Learn Model Transformation Rules from Examples -- Walk Your Tree Any Way You Want -- On an Automated Translation of Satellite Procedures Using Triple Graph Grammars -- The Graph Grammar Library - a generic framework for chemical graph rewrite systems -- Yet Another Three QVT Languages -- Evolution and Synchronisation -- Robust Real-Time Synchronization between Textual and Graphical Editors.
Keywords: Computer science; Software engineering; Logic design; Information Systems; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Management of Computing and Information Systems